Optimasi Produksi Bulanan Menu Best Seller pada UMKM Ayam Penyet JU-PE Menggunakan Linear Programming - Syil Vanna; Guntur Haludin; Joshua Valerio; Oktavian Tri Pandowo; Muhammad Hazel Aqilla Susanto (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This research aims to optimize the monthly production of five best seller menus in Ayam Penyet JU-PE MSMEs to maximize profits in the midst of limited resources, such as raw materials and production capacity. The Linear Programming (LP) method is used to formulate production problems into mathematical models consisting of objective functions and real constraints, such as raw material limitations, production time, and operating capital. Primary data was obtained through direct interviews with business owners, while secondary data was taken from MSME literature and internal documentation. The results of the analysis using the Excel Solver application show that optimal production is achieved by producing 178 servings of tofu per month. This strategy provides a maximum profit of IDR 124,600 and remains within the time limit and available capital. The application of the LP method has proven to be effective in helping MSME actors develop production strategies that are more systematic, efficient, and data-based, so that they can be a reference for future production decision-making.